METHODS FOR IMPROVING THE METHODOLOGY FOR TEACHING TERMINOLOGICAL LEXICON TO STUDENTS IN THE FIELD OF ELECTRICAL ENERGY. (Лучшие интеллектуальные исследования, 2025)
Annotation: This article discusses effective methods for enhancing the teaching of terminological lexicon to students in the field of electrical energy. The study examines various approaches to improve the comprehension and usage of specialized vocabulary necessary for electrical engineering students. The research focuses on identifying the most suitable teaching methods that facilitate better understanding, retention, and application of terminology.